Polemik Keabsahan Naskh Intra-Qur’an dan Ekstra-Qur’an - Sa'dullah Sa'dullah (Jurnal Studi Al-Qur'an, 2022)
The Polemic of the Validity of Intra-Qur'an and Extra-Qur'an Texts. Islamic Education Department, Faculty of Social Sciences, Jakarta State University. Two texts are polemic in this discussion, namely intra-Qur'anic texts (deletion between verses) and extra Qur'anic texts (deletion of the Koran on previous holy books and religions). The naskh polemic occurred because of the uncertainty about whether any verses of the Qur'an were in the text, some acknowledged. Still, others rejected, for various reasons, the mansukh of the poetry of the Qur'an. The term naskh, which means "annulment", was initially used to describe fiqh/Islamic law issues but later developed into the cancellation of pre-Qur'an revelations. Based on this, this study intends to reveal whether the revelation of the Qur'an replaces or cancels all other disclosures so that the concept of naskh is associated with Muhammad's apostolic position regarding the success of saving other monotheistic traditions. The results of this discussion reveal that the focus of the text is not on the cancellation of the verses of the Qur'an (Intra Qur'an). Still, the cancellation of the previous law or sharia (syar'u ma qoblana), either partially or entirely by Islamic law as stated by Al-Jabiri, so that the latter is called the extra text of the Qur'an. However, in general, for the two types of texts, there is still an assumption that the abolition of the previous verse or treatise means denying some of the rules of the text theory itself. It is even considered the same as rejecting the poetry of the Qur'an as the best teaching of religion, as in the QS verse. Al-Baqarah [2]: 106 only expresses the presupposition, not the necessity of the text. Meanwhile, all of the verses of the Qur'an are still valid and cooperative. Even if there is a contradiction, it must be understood proportionally based on socio-historical conditions, not by eliminating verses (Intra-Qur'an texts).